Causal authorship and the equality principle: a defence of the acts/omissions distinction in euthanasia. Issue 4 (1st August 2000) - Stauch, Marc
Abstract : This paper defends the acts/omissions distinction which underpins the present law on euthanasia, from various criticisms (including from within the judiciary itself), and aims to show that it is supported by fundamental principles. After rejecting arguments that deny the coherence and/or legal relevance of the distinction, the discussion proceeds to focus on the causal relationship between the doctor and the patient's death in each case. Although previous analyses, challenging the causal efficacy of omissions generally, are shown to be deficient, it is argued that in certain cases of causing death by omission the causal authorship of the doctor lapses. The final part of the paper examines why this should be morally significant and proposes an answer in terms of the principle of equality. Assuming all other factors are equal, the infringement of this principle provides an additional reason against actively killing a patient, which is not present in cases of passively letting die.